HAK-HAK PEREMPUAN PASCA PERCERAIAN: Nafkah Iddah Talak dalam Hukum Keluarga Muslim Indonesia, Malaysia, dan Yordania - Hammad, Muchammad (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2014)
Regulations regarding divorce idda living in Muslim Family Law (Indonesia, Malaysia and Jordan) in general there is no difference with that found in conventional jurisprudence. Income levels that can be changed according to price inflation not contained in conventional jurisprudence, were living in Muslim Family Laws can be changed. Regulations regarding the divorce waiting period contained living in Muslim Family Law Malaysia and Jordan still better guarantee the rights of women post-divorce compared with existing regulations in Indonesia. [Peraturan mengenai nafkah iddah talak pada Hukum Keluarga Muslim (Indonesia, Malaysia dan Yordania) secara umum tidak ada perbedaan dengan yang terdapat pada fikih konvensional. Kadar nafkah yang dapat berubah sesuai inflasi harga tidak terdapat dalam fiqih konvensional, sedang dalam Hukum Keluarga Muslim nafkah tersebut dapat berubah. Peraturan mengenai nafkah iddah talak yang terdapat dalam UU Keluarga Muslim Malaysia dan Yordania masih lebih menjamin hakhak perempuan pasca perceraian dibandingkan dengan peraturan yang ada di Indonesia.]